Media Exposure and Its Impact on Women's Knowledge in Family Planning Program in Indonesia: Pengaruh Keterdedahan Media terhadap Pengetahuan Wanita Usia Subur dalam Program Keluarga Berencana di Indonesia (Jurnal Komunikasi Pembangunan, 2023)
Utilization of the mass media as a source of development information is a strategic way to ensure the success of the Family Planning (KB) program in Indonesia. Therefore, access to information on family planning and contraceptive use is an important factor in increasing knowledge of the society. This study aims to examine the correlation between the level of exposure of the mass media and the level of knowledge of women about modern contraceptives. By utilizing secondary data sourced from National Population and Family Planning Agency (BKKBN) that so called “Survey Kinerja dan Akuntabilitas Program” in the year 2019, this study also conducted an inferential statistical test through a linear regression test to see the effect between variables. The respondents in this study were Women of Childbearing Age, accounted for 59,982 women, which was the result of data collection from 34 provinces and 514 cities/districts in Indonesia. The results of this study showed that the level of media exposure had a positive effect on increasing women knowledge about family planning. The media exposure level is also influenced by characteristic of women regarding age, education and level of wealth.